SOCIODEMOGRAPHIC AND LIFESTYLE FACTORS IN PRE- AND POSTMENOPAUSAL PATIENTS WITH BREAST CANCER - Gomes Filho, José Euderaldo Costa; Rocha, Ariane Silva da; Fernandes, Gisele Aparecida; López, Rossana Verónica Mendoza; Curado, Maria Paula (Mastology, 2021)
To analyze pre- and postmenopausal patients with breast cancer with regard to sociodemographic factors. This is a crosssectional study with 705 patients with breast cancer. Patients aged 50 years and older accounted for 55.9% (n=394), whereas those aged 50 years or younger accounted for 44.1% (n=311). For both pre- and postmenopausal patients, there is greater proportional access through the Unified Health System (SUS), 62.7% (n=195) and 51.5% (n=203) (p=0.002); married, 65.9% (n=205) and 52.8% (n=208) (p<0.001); white ethnicity, 75.9% (n=236) and 77 (n=302) (p=0.623); and undergraduate level, 48.1% (n=149) and 40.1% (n=158) (p<0.001). For 82.7% (n=272) of the SUS participants and 80.9% (n=276) of those with complementary health care (p<0.001), the first mammogram was performed between the ages of 18 and 40 years; own housing for 74.2% (n=230) and 85.6% (n=333) (p<0.001), denied tobacco use, 78.1% (n=243) and 64.8% (n=254) (p<0.001); and alcohol consumption, 76.2% (n=237) and 86.2% (n=337) (p<0.001); the reference of cancer cases in the family occurred in 55.9% (n=118) and 63.7% (n=174) (p=0.300); however, breast cancer cases were reported in only 44.1% (n=93) and 36.3% (n=99) (p=0.187); the body mass index (BMI) was considered eutrophic, 43.7% (n=136) and 37.9% (n=149) (p<0.001). The pre- and postmenopause results showed differences regarding access to treatment, marital status, education, housing, first mammogram, alcohol and tobacco consumption, and BMI. Therefore, sociodemographic and lifestyle factors show a difference in patients with breast cancer in pre- and postmenopause.